Factors Influencing Employee Turnover Intention in Nepalese Garment Industries - Gurung, Kushal; Rawat, Ramesh (Nepalese Journal of Management, 2025)
This study examines the factors influencing employee turnover intention in Nepalese garment industries. Employee turnover intention is the dependent variable. The selected independent variables are wages, alternative job opportunities, workplace culture, job satisfaction, working conditions, perceived organizational support, and leadership style. The primary source of data is used to assess the opinions of respondents regarding wages, alternative job opportunities, workplace culture, job satisfaction, working conditions, perceived organizational support, leadership style, and employee turnover intention. The study is based on primary data of 164 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of employee turnover intention in Nepalese garment industries. The study showed a negative impact of wages on employee turnover intention indicating that higher the wages, lower would be the employee turnover intention. Similarly, the study showed a positive impact of alternative job opportunity on employee turnover intention. It indicates that higher the alternative job opportunity, higher would be the employee turnover intention. Likewise, the study revealed a negative impact of working conditions on employee turnover intention. It indicates that better working conditions lead to decrease in employee turnover intention. Further, the study showed a negative impact of job satisfaction on employee turnover intention. It indicates that higher the job satisfaction, lower would be the employee turnover intention. In addition, the study also showed a negative impact of workplace culture on employee turnover intention. It indicates that supportive work culture leads to decrease in employee turnover intention. Moreover, the study showed a negative impact of perceived organizational support on employee turnover intention. It indicates that increase the employee’s affective attachment to the organization leads to decrease in employee turnover intention. Further, the study revealed a negative impact of leadership style on employee turnover intention. It indicates that supportive behavioral approach employed by leaders lead to decrease in employee turnover intention.